2022
DOI: 10.1108/ijchm-12-2021-1544
|View full text |Cite
|
Sign up to set email alerts
|

What have hosts overlooked for improving stay experience in accommodation-sharing? Empirical evidence from Airbnb customer reviews

Abstract: Purpose In accommodation-sharing, hosts must provide satisfactory stay experiences for guests, who will then express intentions to revisit (behavioral loyalty) and/or recommend the experiences to others (attitudinal loyalty) in their reviews. Through the lens of expectation-confirmation theory, this study aims to investigate the service dimensions customers focus on in their reviews and their relationships with customer-loyalty manifestations in accommodation-sharing. Design/methodology/approach This study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…However, the role of the host in the Airbnb context varies, and good communication is crucial for building trust, while guests value privacy and safety, which are more commonly guaranteed in hotels. Lee et al (2023) identified four themes -"amenities," "host," "location," and "information"and confirmed their importance in accommodation-sharing. While locational benefits were found to be important, customers who express intentions to re-visit or recommend the experiences to others may not mention such benefits in their reviews.…”
Section: Impact On the Local Communitymentioning
confidence: 65%
See 2 more Smart Citations
“…However, the role of the host in the Airbnb context varies, and good communication is crucial for building trust, while guests value privacy and safety, which are more commonly guaranteed in hotels. Lee et al (2023) identified four themes -"amenities," "host," "location," and "information"and confirmed their importance in accommodation-sharing. While locational benefits were found to be important, customers who express intentions to re-visit or recommend the experiences to others may not mention such benefits in their reviews.…”
Section: Impact On the Local Communitymentioning
confidence: 65%
“…Studies show that trust is a vital factor facilitating users' willingness to engage in interactions, and it can be developed in SE through social and technical enablers (such as social referrals, quality of information and transaction safety) that are relevant to consumer development of trust (Kong et al, 2020;Yang et al, 2019;Farmaki and Stergiou, 2019). Hosts can be considered as a vital part of the Airbnb experience (Lee et al, 2023;Del Chiappa et al, 2021;Petruzzi et al, 2020;Kiatkawsin, 2020) Social interactions help in developing trust Latif et al, 2019;Jiang et al, 2019) which can easily be developed before arriving at the destination if the host had the same nationality as the guest (Kas et al, 2022) or the guests got in touch with the host through messaging the host, and after booking is confirmed they can use social media to get to know each other (Moon et al, 2019), they would feel more satisfied when they are able to check the host's profile, ensure that the account is verified and communication is done smoothly, this will increase the satisfaction level (Sthapit et al, 2019;Zhu et al, 2019). Guests would cancel their booking if they didn't feel comfortable with any safety or communication factors (Del Chiappa et al, 2021).…”
Section: Guest-host Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Thakur et al (2022) performed predictive modeling of Airbnb units in Rio de Janeiro using a deep neural network to identify the influential features. Combinations of hedonic modeling and quantitative techniques for discovering the rental price IJCHM 35,10 determinants of Airbnb units have been documented (Sainaghi et al, 2021;Lee et al, 2022;Wang and Rasouli, 2022). Text mining approaches have also been used to comprehend related issues driving rental prices (Yu et al, 2021;Zhang et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vayghan et al (2022) analyze the underlying consumer values that encourage app users to interact with it more and keep using it to book hotels. Lee et al (2023) affirm that in accommodation sharing, the host must ensure that guests have a positive experience so they would express the intention to return (behavioral loyalty) and recommend it to others (attitudinal loyalty) on the Internet.…”
Section: Introductionmentioning
confidence: 99%